2007
DOI: 10.1590/s1516-31802007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Hysteroscopy as a standard procedure for assessing endometrial lesions among postmenopausal women

Abstract: CONTEXT AND OBJECTIVES: Endometrial cancer is the most prevalent type of malignant neoplasia of the genital tract. The objective of this study was to calculate the sensitivity, specificity, accuracy and positive and negative predictive values for diagnostic hysteroscopy, in comparison with histopathological tests, for all lesions of the endometrial cavity. DESIGN AND SETTING: Retrospective descriptive study at the public tertiary-level university hospital of Faculdade de Medicina de Ribeirão Preto, Universidad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
5
16
0
7
Order By: Relevance
“…Ribeiro et al [12] reported only one carcinoma (0.25%) in 399 asymptomatic patients who underwent hysteroscopy and questioned the utility of ultrasound among asymptomatic women. Our experience, on the other hand, favors sonographic screening in these women since we found higher rates of carcinoma and endometrial hyperplasia (2.9% and 3.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Ribeiro et al [12] reported only one carcinoma (0.25%) in 399 asymptomatic patients who underwent hysteroscopy and questioned the utility of ultrasound among asymptomatic women. Our experience, on the other hand, favors sonographic screening in these women since we found higher rates of carcinoma and endometrial hyperplasia (2.9% and 3.5%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of endometrial cancer that is seen in the literature is generally higher. 31 Abnormal peri and postmenopausal bleeding is associated with endometrial cancer in about 10% of cases. 32 The lower incidence in our study was may be due to the patients with postmenopausal bleeding were taken up for fractional curettage, which is still opted by many of the gynecologists in our setup.…”
Section: 23mentioning
confidence: 99%
“…This data was supported by many studies. 2,8 It is apparent that hysteroscopy is much more sensitive than TVS in the detection of focal endometrial pathology, and the specificity of hysteroscopy is more than TVS in diagnosing various endometrial conditions (98.5 and 93.3% respectively) ( Table 5).…”
Section: Discussionmentioning
confidence: 99%